Analisis Motivasi Belajar Matematika Peserta didik Kelas IX SMPIT Abdan Syakuro Lampu Iman - Indriyanto, Dimas Dwi (Papanda, 2025)
This research aims to analyze the level of motivation to learn mathematics of grade IX students at SMPIT Abdan Syakuro Lampu Iman. Learning motivation is an important internal factor that can determine the success of students in understanding and mastering learning materials, especially in mathematics subjects. This study used a descriptive qualitative approach with 27 students as research subjects. Data were collected using an instrument in the form of a learning motivation questionnaire based on six indicators proposed by Hamzah B. Uno, namely: desire to succeed, future expectations, learning encouragement, appreciation, interesting activities, and conducive learning environment. The results showed variations in the level of learning motivation in each indicator. Most students have sufficient motivation to learn, although there are still limitations in the aspects of independent reference search, participation in group activities, and attention to additional tasks. This finding confirms the importance of learning approaches that are able to stimulate learning motivation from various aspects. This research is expected to be the basis for designing more effective learning strategies.